EATING BEHAVIOUR OF SHEEP FED AT DAY AND/OR NIGHT PERIOD - Nugroho, T. A.; Dilaga, W. S.; Purnomoadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
The aim of this research was to determine the eating behavior of sheep which fed at day and/or night period. Twelve ram average body weight 20.65 + 1.89 kg, CV = 9.15%, and age ranged from 12 to 18 months were used in this study. Rams were daily fed pelleted diet at 5% of body weight (BW) in 100% dry matter base. Animals were assigned to Completely Randomized Design and divided into three groups for different feeding time treatments. The treatments were day feeding time (feeding allowed from 0600 to 1800; T0618), night feeding (from 1800 to 0600; T1806) and whole-day feeding (24 h; T0606), respectively. Parameters observed in this study were duration of eating, rumination, rest, standing and laying activity (minute/day), dry matter intake (DMI, g/day) and eating speed (g/minute). Collected data were analyzed using ANOVA with F-test and if significantly was found were then analyzed with Duncan test. The results showed that eating duration (89.71 min/day) and DMI (1034.53 g/day) on T1806 were significantly lower (P<0.05) than T0618 (117.78 min/day; 1208.75 g/day) and T0606 (127.5 min/day; 1281.63 g/day) but, the other observation of ruminating, rest, standing and laying duration and eating speed were found not significantly different in the all treatments. It can be concluded that feeding at night period can reduce eating time significantly compared to feeding during the day period or 24 hours a day, although it results in decreasing feed consumption.